CP-156 Evolution of consumption of three antibiotics classes and of the resistance of escherichia coli to these classes. (25th February 2017) - Cheikh, A; Bouatia, M; Ababou, A; Cherrah, Y; Benaouda, A; Hassani, A El
Abstract : Background: Antibiotic bacterial resistance is one of the major challenges for hospitals worldwide. Escherichia coli ( E coli ) is the main bacterial germ in healthcare services in our hospital. this bacteria has changed its sensitivity to different antibiotic classes remarkably in the last decades. Purpose: Our objective was to study consumption of three classes of antibiotics: penicillins (amoxicillin and amoxicillin/clavulanic acid), cephalosporines (ceftriaxone and ceftazidim) and quinolones (ciprofloxacin), and also to study the evolution of E coli resistance to these three classes of antibiotics. Material and methods: We studied consumption of the three antibiotic classes using daily defined dose (DDD) per 1000 hospitalisation days between 2006 and 2015. Also, we monitored the change in E coli resistance to these three classes between 2009 and 2015 using the WHONET 5.3 percentage of resistant strains with respect to all the strains collected. Results: 3603 E coli strains were collected (57% of BGN). Consumption of the three antibiotics classes and E coli resistance to these molecules are summarised in the table. Conclusion: E coli resistance to the three antibiotic classes has increased over the years. Selection pressure is one of the most important reasons for this evolution of resistance and the high antibiotic consumption. The increasing resistance of E coli to penicillins has pushed consumption towards other classes, such as the cephalosporines and quinolones, increasing consumption of these two classes which will undoubtedly accelerate the emergence of bacterial resistance phenomenon to cephalosporins and fluoroquinolones. Consequently, close monitoring of antibiotic consumption must be established by hospital pharmacists. References and/or acknowledgements: Acknowledgements to microbiology team. No conflict of interest